CALORIE RESTRICTION MODIFIES UBIQUINONE AND COQ TRANSCRIPTS LEVELS IN MOUSE TISSUES - Parrado, Cristina (2011)
We studied ubiquinone (Q), Q homologue ratio and steady-state levels of mCOQ transcripts in tissues from mice fed ad libitum or under calorie restriction. Maximum ubiquinone levels on a protein basis were found in kidney and heart, followed by liver, brain and skeletal muscle. Liver and skeletal muscle showed the highest Q(9)/Q(10) ratios with significant inter-individual variability. Heart, kidney, and particularly brain exhibited lower Q(9)/Q(10) ratios and inter-individual variability. In skeletal muscle and heart, the most abundant mCOQ transcript was mCOQ7, followed by mCOQ8, mCOQ2, mPDSS2, mPDSS1 and mCOQ3. In non muscular tissues (liver, kidney and brain) the most abundant mCOQ transcript was mCOQ2, followed by mCOQ7, mCOQ8, mPDSS1, mPDSS2, and mCOQ3. Calorie restriction increased both ubiquinone homologues and mPDSS2 mRNA in skeletal muscle, but mCOQ7 was decreased. In contrast, Q(9) and most mCOQ transcripts were decreased in heart. Calorie restriction also modified Q(9)/Q(10) ratio, which was increased in kidney and decreased in heart without alterations of mPDSS1 or mPDSS2 transcripts. We demonstrate for the first time that unique patterns of mCOQ transcripts exist in muscular and non-muscular tissues, and that Q and COQ genes are targets of calorie restriction in a tissue-specific way.